2018
DOI: 10.21894/jopr.2018.0022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Palm-Based High-Oleic Blended Cooking Oil Diet on Selected Biomarkers of Inflammation and Obesity Compared to Extra Virgin Olive Oil Diet in Overweight Malaysian Adults

Abstract: High-oleic blended cooking oil (HOBO) comprises palm olein and canola oil, with more than 50% of monounsaturated oleic acid. Studies on the effects of HOBO on human health is limited and therefore, this study compared the effects of HOBO, extra virgin olive oil (OO) and coconut oil (CO) on biomarkers of inflammation, obesity and blood pressure in 32 overweight but otherwise healthy Malaysian adults. Subjects were randomised to receive three different dietary sequences, each comprising three six-week dietary pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The characteristics of the included studies are shown in Table 1. Among the 52 studies selected, 44 7,17–21,28–66 are randomized clinical trials with a parallel design and eight 67–74 have a crossover design. The samples of the included studies ranged from 23 to 351 participants, with a mean age ranging from 23 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. Among the 52 studies selected, 44 7,17–21,28–66 are randomized clinical trials with a parallel design and eight 67–74 have a crossover design. The samples of the included studies ranged from 23 to 351 participants, with a mean age ranging from 23 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the assertion that the consumption of a high amount of saturated fats from palm oil is linked with cardiovascular diseases, studies revealed that there is no concrete evidence associating palm oil intake with the risk of heart disease or the negative impact on children's health [72,73]. Furthermore, the link between the dietary intake of palm oil and obesity, in comparison with other vegetable oils, is not supported by adequate evidence [74][75][76]. There is also no scientific proof to validate the association between palm oil intake and the incidence of cancer [77].…”
Section: Health Sustainabilitymentioning
confidence: 99%